Factors affecting revisit intention in outpatient care in private hospital in Indonesia: Narrative Review - Antonio, Yane Margaretha; Permanasari , Vetty Yulianty (Syntax Corporation Indonesia, 2025)
This narrative review examines the factors influencing revisit intentions among outpatient care patients in private hospitals in Indonesia. The study highlights the significance of service quality, patient satisfaction, trust, and effective complaint handling in shaping patients' willingness to return. Key findings indicate that while technical service quality is vital, non-clinical aspects such as communication, social media engagement, and queue management also play critical roles. Understanding these determinants is essential for hospitals aiming to enhance patient loyalty and ensure competitive healthcare services.